Wheat production in Bangladesh: technological, economic and policy issues - Morris, Michael L.; Chowdhury, Nuimuddin; Meisner, Craig A. (International Food Policy Research Institute, 1997)
Since the early 1970s, sustained government investment in irrigation facilities, rural infrastructure, agricultural research, and extension services has helped Bangladeshi farmers achieve dramatic increases in food production. Today Bangladesh is nearing self-sufficiency in rice, the major staple. Production of wheat, the second most important cereal, has also increased, although the country still imports significant quantities of wheat to meet rapidly growing domestic demand. While the government of Bangladesh continues to provide strong support to rice producers, its commitment to wheat farmers seems less firm. Some policymakers have gone so far as to question whether support to wheat should be scaled back, citing studies showing that wheat production is unprofitable and represents an inefficient use of resources. But is wheat production in Bangladesh really unprofitable for farmers and inefficient for the country? Researchers from the International Food Policy Research Institute (IFPRI) and the International Maize and Wheat Improvement Center (CIMMYT) recently examined the arguments for and against wheat production in Bangladesh. In Wheat Production in Bangladesh: Technological, Economic, and Policy Issues, Research Report 106, Michael L. Morris, Nuimuddin Chowdhury, and Craig Meisner used a combination of financial and economic analysis to compare production of two irrigated crops (wheat and boro rice) and three nonirrigated crops (wheat, oilseeds, and pulses) in five wheat-growing zones. Their goal was to determine the extent to which government policies and market failures may have driven a wedge between financial and economic profitability. Whenever financial and economic profitability diverge, farmers experience distorted incentives, and policy reforms may be necessary to encourage them to act in ways that are consistent with efficiency objectives.